A Porous Pyrochlore Y2[Ru1.6Y0.4]O7–δ Electrocatalyst for Enhanced Performance towards the Oxygen Evolution Reaction in Acidic Media. Issue 42 (19th September 2018) - Kim, Jaemin; Shih, Pei‐Chieh; Qin, Yao; Al‐Bardan, Zaid; Sun, Cheng‐Jun; Yang, Hong
Abstract: A robust porous structure is often needed for practical applications in electrochemical devices, such as fuel cells, batteries, and electrolyzers. While templating approach is useful for the preparation of porous materials in general, it is not effective for the synthesis of oxide‐based electrocatalysts owing to the chemical instability of disordered porous materials thus created. Now the synthesis of phase‐pure porous yttrium ruthenate pyrochlore oxide using an unconventional porogen of perchloric acid is presented. The lattice oxygen defects are formed by the mixed‐valence state of Ru 4+/5+ through the partial substitution of Ru 4+ with Y 3+ cations, leading to the formation of mixed B‐site Y2 [Ru1.6 Y0.4 ]O7− δ . This porous Y2 [Ru1.6 Y0.4 ]O7− δ electrocatalyst exhibits a turnover frequency (TOF) of 560 s −1 (at 1.5 V versus RHE) for the oxygen evolution reaction, which is two orders of magnitude higher than that of the RuO2 reference catalyst (5.41 s −1 ). Abstract : Porous Y2 [Ru1.6 Y0.4 ]O7− δ pyrochlore oxide was synthesized using perchloric acid as the unconventional porogen. This pyrochlore exhibited excellent activity towards oxygen evolution reaction (OER) in acid media, with a turnover frequency (TOF) of 560 s −1 (at 1.5 V versus RHE) on the Ru site. A high porous surface area and lattice oxygen defects (due to the partial substitution of B‐site Ru 4+ with Y 3+ ) are important for the enhanced OER activity.